Analisis Transaksi Pasar Valuta Asing (Al-Sharf) Pada Bank Syariah Melalui Aplikasi Perbankan - Indah Datin Nadliroh; Mudji (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2024)
This study aims to determine the Islamic foreign exchange system (Al-Sharf) in Islamic banks and the views of Islamic banks on foreign currency exchange contracts in accordance with the principles that apply in Islamic teachings (Sharia). This research is a type of literature study research. The literature study method is a series of activities related to methods of collecting library data, reading and taking notes, and managing research materials. The results of this study indicate that the practice of buying and selling foreign currency (Al-Sharf) according to the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) is permissible if it is done on the basis of mutual consent between the two parties and in cash (spot). With foreign exchange transactions carried out in cash, the gharar in the al-sharf contract will disappear. Attacks on Islamic Banks in implementing foreign exchange trading applications, banks are essentially institutional intermediaries between savers and investors. However, Islamic banks must fulfill sharia provisions based on applicable teachings.